Calculating the aerodynamics of vertical axis wind turbines - Ngoc, Hoang Thi Bich (Vietnam Journal of Mechanics, 2012)
Vertical axis wind turbine technology has been applied last years, very long after horizontal axis wind turbine technology. Aerodynamic problems of vertical axis wind machines are discussible. An important problem is the determination of the incidence law in the interaction between wind and rotor blades. The focus of the work is to establish equations of the incidence depending on the blade azimuth, and to solve them. From these results, aerodynamic torques and power can be calculated. The incidence angle is a parameter of velocity triangle, and both the factors depend not only on the blade azimuth but also on the ratio of rotational speed and horizontal speed. The built computational program allows theoretically selecting the relationship of geometric parameters of wind turbine in accordance with requirements on power, wind speed and installation conditions.